2021
DOI: 10.12998/wjcc.v9.i9.2047
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Association for the Study of Pain: Experts consensus on ultrasound-guided injections for the treatment of spinal pain in China (2020 edition)

Abstract: Spinal pain (SP) is a common condition that has a major negative impact on a patient’s quality of life. Recent developments in ultrasound-guided injections for the treatment of SP are increasingly being used in clinical practice. This clinical expert consensus describes the purpose, significance, implementation methods, indications, contraindications, and techniques of ultrasound-guided injections. This consensus offers a practical reference point for physicians to implement successfully ultrasound-guided inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“… 31 Studies have shown that the combination of dexmedetomidine and an opioid in analgesic pumps has a synergistic effect that greatly reduces the amount of opioids required. 32 Dexmedetomidine with opioids also reduces postoperative pain scores as well as the incidence of nausea and vomiting and other adverse events such as hypotension and drowsiness. 33 In addition, it reduces the length of hospital stay and improves patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Studies have shown that the combination of dexmedetomidine and an opioid in analgesic pumps has a synergistic effect that greatly reduces the amount of opioids required. 32 Dexmedetomidine with opioids also reduces postoperative pain scores as well as the incidence of nausea and vomiting and other adverse events such as hypotension and drowsiness. 33 In addition, it reduces the length of hospital stay and improves patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…21 Recently, expert consensus in China offers a practical reference to implement successful USguided injections in the treatment of chronic spinal pain. 22 Cervical nerve root injection for the treatment of CRP under the US guidance has been investigated by many researchers. [23][24][25][26][27] In the present study, we performed cervical TFSI under US guidance using a similar approach to Yuexiang Wang.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, there has been a growing trend in the application of ultrasonography in chronic pain management, because US provides direct visualization of soft tissue, peripheral nerve, blood flow, and real-time needle advancement and avoids exposure to the risks of radiation 21. Recently, expert consensus in China offers a practical reference to implement successful US-guided injections in the treatment of chronic spinal pain 22. Cervical nerve root injection for the treatment of CRP under the US guidance has been investigated by many researchers 23–27…”
Section: Discussionmentioning
confidence: 99%
“…We read the article by Wang et al [ 1 ] with great interest, in which the authors proposed a protocol for physicians to administer ultrasound-guided injections as treatment for spinal pain. Spinal pain is highly prevalent in the general population and often causes substantial suffering, many lost workdays, and high medical costs[ 2 ].…”
Section: To the Editormentioning
confidence: 99%